A study on factors that contribute to the level of employee turnover at Shapadu Energy and Engineering Sdn Bhd (Teluk Kalong Yard) / Nor Amalina Mat Hussain - Mat Hussain, Nor Amalina (Faculty of Business and Management, 2014)
This research was conducted for the purpose of “A Study on Factors That Contribute to the Level of Employee Turnover at Shapadu Energy and Engineering Sdn Bhd (Teluk Kalong Yard)”. The main objective of this research was to identify the factors that contribute to the Level of employee turnover at Shapadu Energy and Engineering Sdn Bhd (Teluk Kalong Yard). The respondent of this study was from Shapadu Energy and Engineering Sdn Bhd (Teluk Kalong Yard) employees. A questionnaire had been distributed to those who work at Shapadu Energy and Engineering Sdn Bhd (Teluk Kalong Yard) which is 70 respondents. The data was obtained from primary data by using questionnaire. It has five sections in the questionnaire consist of Section A for demographic profile, Section B for dependent variable which is Employee Turnover. While the other three section consist of independent variables which is Section C for Wages, Section D for Better Job Offer and Section E for Job Stress. The researcher was analyze the data by using SPSS 16.0 in order to identify the mean, median, standard deviation, reliability test, correlation testing and regression analysis. At the end of the result, the researcher found that all of the hypotheses are supported.